Excess charge-carrier induced instability of hybrid perovskites. Issue 1 (December 2018) - Lin, Yuze; Chen, Bo; Fang, Yanjun; Zhao, Jingjing; Bao, Chunxiong; Yu, Zhenhua; Deng, Yehao; Rudd, Peter; Yan, Yanfa; Yuan, Yongbo; Huang, Jinsong
Abstract Identifying the origin of intrinsic instability for organic–inorganic halide perovskites (OIHPs) is crucial for their application in electronic devices, including solar cells, photodetectors, radiation detectors, and light-emitting diodes, as their efficiencies or sensitivities have already been demonstrated to be competitive with commercial available devices. Here we show that free charges in OIHPs, whether generated by incident light or by current-injection from electrodes, can reduce their stability, while efficient charge extraction effectively stabilizes the perovskite materials. The excess of both holes and electrons reduce the activation energy for ion migration within OIHPs, accelerating the degradation of OIHPs, while the excess holes and electrons facilitate the migration of cations or anions, respectively. OIHP solar cells capable of efficient charge-carrier extraction show improved light stability under regular operation conditions compared to an open-circuit condition where the photo-generated charges are confined in the perovskite layers. Optoelectronic devices based on organic–inorganic halide perovskites show promising performance, but their poor stability impedes the commercialization. Here Lin et al. show that excess free charges are detrimental and efficient charge-carrier extraction is necessary for improved device stability.